Youth Participation in Preserving the Jaranan Ritual Tradition in Malang, Indonesia - Cindy Khoirun Nisa; Rizki Agung Novariyanto; Lina Desriana Pratiwi (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2026)
Jaranan art as part of local cultural heritage faces significant challenges in the era of globalization, particularly the declining interest of younger generations and the gradual shift of sacred ritual values within its performances. This study aims to analyze youth participation in preserving the ritual tradition of Jaranan Putro Gunung Sari and to examine the strategies employed to sustain its cultural continuity amid social change and modernization. Previous studies have largely focused on the symbolic meanings and general preservation of Jaranan culture, while limited attention has been given to the role of youth as key actors in maintaining the continuity of ritual traditions. This research employs a descriptive qualitative method through interviews, observations, and documentation. The findings reveal that the Jaranan ritual functions as a social fact that strengthens collective consciousness and community solidarity. Furthermore, youth involvement reflects a form of cultural agency in safeguarding local cultural identity through various preservation strategies, including intergenerational regeneration, collective deliberation, and the use of social media for cultural promotion. The study demonstrates that the sustainability of traditional arts depends not only on cultural inheritance but also on the active participation and adaptive capacity of younger generations in responding to contemporary social transformations. This research contributes to the discourse on cultural sociology and youth-based cultural preservation in traditional ritual arts.